Family history of diabetes, lifestyle factors, and the 7‐year incident risk of type 2 diabetes mellitus in middle‐aged Japanese men and women. Issue 3 (13th February 2013) - Sakurai, Masaru; Nakamura, Koshi; Miura, Katsuyuki; Takamura, Toshinari; Yoshita, Katsushi; Sasaki, Satoshi; Nagasawa, Shin‐ya; Morikawa, Yuko; Ishizaki, Masao; Kido, Teruhiko; Naruse, Yuchi; Suwazono, Yasushi; et al.
Abstract Aims/Introduction This cohort study of middle‐aged Japanese participants investigated the relationship between family history of diabetes, the incident risk of type 2 diabetes and the interaction of these variables with other factors. Materials and Methods Study participants were 3, 517 employees (2, 037 men and 1, 480 women) of a metal products factory in Japan. Baseline health examinations included questions about medical history, physical examination, anthropometric measurements, questions about lifestyle factors, such as smoking, alcohol consumption and habitual exercise, and a self‐administered diet history questionnaire. Family history of diabetes was defined as having at least one‐first‐degree relative with diabetes. The incidence of diabetes was determined in annual medical examinations over a 7‐year period. Hazard ratios (HRs) for type 2 diabetes were estimated by Cox proportional hazards analysis. Results Of the 3, 517 participants, 630 (18%) had a family history of diabetes mellitus. During the study, 228 participants developed diabetes. The age and sex‐adjusted HR for type 2 diabetes in participants with a family history of diabetes was 1.82 (95% confidence interval 1.36–2.43) as compared with those without a family history of diabetes. HRs did not change after adjustment for body mass index and lifestyle factors. We found no interactions with body mass index, insulin resistance, pancreatic β‐cell function or lifestyle factors. Conclusions Family history of diabetes was associated with the incident risk of diabetes, and these associations were independent of other risk factors, such as obesity, insulin resistance, and lifestyle factors in Japanese men and women.